2021
DOI: 10.1177/13591045211064134
|View full text |Cite
|
Sign up to set email alerts
|

Home direct-to-consumer telehealth solutions for children with mental health disorders and the impact of Covid-19

Abstract: Delivery of mental health treatment in the home can close gaps in care. Telehealth also provides access to healthcare that has been disrupted due to the COVID-19 pandemic. In 2016, a home direct-to-consumer telehealth program was initiated. Mental health encounters made up a significant portion of all telehealth encounters and COVID-19 had a significant impact on accelerating the utilization of telehealth. Telemental health has been more successful at meeting targeted volumes than the overall health system. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The remaining papers were focused on behaviour programmes (e.g. behaviour counselling, applied behavioural analysis therapy; n = 9), 54–62 speech and language therapy ( n = 4), 63–66 physiotherapy ( n = 3), 53,67,68 mental health support ( n = 2), 69,70 auditory‐verbal therapy for children and young people with a hearing impairment ( n = 1), 71 rehabilitative therapy for children and young people with vision impairment ( n = 1), 72 and early intervention coaching ( n = 1) 73 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining papers were focused on behaviour programmes (e.g. behaviour counselling, applied behavioural analysis therapy; n = 9), 54–62 speech and language therapy ( n = 4), 63–66 physiotherapy ( n = 3), 53,67,68 mental health support ( n = 2), 69,70 auditory‐verbal therapy for children and young people with a hearing impairment ( n = 1), 71 rehabilitative therapy for children and young people with vision impairment ( n = 1), 72 and early intervention coaching ( n = 1) 73 …”
Section: Resultsmentioning
confidence: 99%
“…The remaining papers were focused on behaviour programmes (e.g. behaviour counselling, applied behavioural analysis therapy; n = 9), [54][55][56][57][58][59][60][61][62] speech and language therapy (n = 4), [63][64][65][66] physiotherapy (n = 3), 53,67,68 mental health support (n = 2), 69,70 auditory-verbal therapy for children and young people with a hearing impairment (n = 1), 71 rehabilitative therapy for children and young people with vision impairment (n = 1), 72 and early intervention coaching (n = 1). 73 The percentages of families reporting attending a telehealth appointment with an AHP tended to be lower (less than 50% of study samples) than those reported for medical care appointments (over 50% of study samples).…”
Section: Frequency Of Consultationsmentioning
confidence: 99%
“…In addition, most families who completed treatment came from married households. Perhaps single-parent households face barriers that interfere with attendance, such as childcare for siblings or work-related responsibilities, and other ways of involving parents in treatment may be warranted (e.g., telehealth; Khanna & Carper, 2022; Norman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, digital tools were welcomed as a solution to problems including social stigma and a mismatch between demand and supplies for mental healthcare. Instead of the traditional mental health treatment paradigm, it was predicted that digital technologies would provide more flexible, accessible, inexpensive, and maybe less stigmatizing alternatives (Norman et al, 2022). Flexible approaches were urgently needed as a consequence of the lack of access to mental healthcare (Myran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%